Automatic and Deliberate Affective Associations with Sexual Stimuli in Women with Lifelong Vaginismus Before and After Therapist‐Aided Exposure Treatment. (1st March 2014) - Melles, Reinhilde J.; ter Kuile, Moniek M.; Dewitte, Marieke; van Lankveld, Jacques J.D.M.; Brauer, Marieke; de Jong, Peter J.
Abstract: Introduction: The intense fear response to vaginal penetration in women with lifelong vaginismus, who have never been able to experience coitus, may reflect negative automatic and deliberate appraisals of vaginal penetration stimuli which might be modified by exposure treatment. Aims: The aim of this study is to examine whether (i) sexual stimuli elicit relatively strong automatic and deliberate threat associations in women with vaginismus, as well as relatively negative automatic and deliberate global affective associations, compared with symptom‐free women; and (ii) these automatic and more deliberate attitudes can be modified by therapist‐aided exposure treatment. Methods: A single target Implicit Association Test (st‐IAT) was used to index automatic threat associations, and an Affective Simon Task (AST) to index global automatic affective associations. Participants were women with lifelong vaginismus (N = 68) and women without sexual problems (N = 70). The vaginismus group was randomly allocated to treatment (n = 34) and a waiting list control condition (n = 34). Main Outcome Measures: Indices of automatic threat were obtained by the st‐IAT and automatic global affective associations by the AST, visual analogue scales (VAS) were used to assess deliberate appraisals of the sexual pictures (fear and global positive affect). Results: More deliberate fear and less global positive affective associations with sexual stimuli were found in women with vaginismus. Following therapist‐aided exposure treatment, the strength of fear was strongly reduced, whereas global positive affective associations were strengthened. Automatic associations did not differ between women with and without vaginismus and did not change following treatment. Conclusions: Relatively stronger negative (threat or global affect) associations with sexual stimuli in vaginismus appeared restricted to the deliberate level. Therapist‐aided exposure treatment was effective in reducing subjective fear of sexual penetration stimuli and led to more global positive affective associations with sexual stimuli. The impact of exposure might be further improved by strengthening the association between vaginal penetration and positive affect (e.g., by using counter‐conditioning techniques).